Effect of the Apulia air quality plan on PM10 and benzo(a)pyrene exceedances - L. Trizio; L. Angiuli; M. Menegotto; F. Fedele; R. Giua; F. Mazzone; A.G.C. Carducci; R. Bellotti; G. Assennato (Global Journal of Environmental Science and Management)
During the last years, several exceedances of PM10 and benzo(a)pyrene limit values exceedances were recorded in Taranto, a city in southern Italy included in so-called areas at high risk of environmental crisis because of the presence of a heavy industrial district including the largest steel factory in Europe. A study of these critical pollution events showed a close correlation with the wind coming from the industrial site to the adjacent urban area. During 2011, at monitoring sites closes to the industrial area, at least the 65% of PM10 exceedances were related to wind day conditions (characterized by at least 3 consecutive hours of wind coming from 270-360±2deg with an associated speed higher than 7 m/s). For this reason, in 2012 an integrated environmental permit and a regional air quality plan were enacted to reduce pollutant emissions from industrial plants. A study of PM10 levels registered during windy days was performed during critical episodes of pollution highlighting that the difference between windy days and no windy days’ concentrations reduces from 2012 to 2014 in industrial site. False negative events (verified ex-post by observed meteorological data) not identified by the forecast model - did not show a significant influence on PM concentration: PM10 values were comparable and sometimes lower than windy days levels. It is reasonable that the new scenario with a relevant reduction emissions form Ilva plant reduced the pollutants contribution from industrial area, contributing to PM10 levels decrease, also in false negative events.